Face-Evoked Steady-State Visual Potentials: Effects of Presentation Rate and Face Inversion - Gruss, L. Forest; Wieser, Matthias J.; Schweinberger, Stefan; Keil, Andreas (Frontiers in Human Neuroscience, 2012)
Face processing can be explored using electrophysiological methods. Research with event-related potentials (ERPs) has demonstrated the so-called face inversion effect, in which the N170 component is enhanced in amplitude and latency to inverted, compared to upright, faces. The present study explored the extent to which repetitive lower-level visual cortical engagement, reflected in flicker steady-state visual evoked potentials (ssVEPs), shows similar amplitude enhancement to face inversion. We also asked if inversion related ssVEP modulation would be dependent on the stimulation rate at which upright and inverted faces were flickered. To this end, multiple tagging frequencies were used (5, 10, 15, and 20 Hz) across two studies (n = 21, n = 18). Results showed that amplitude enhancement of the ssVEP for inverted faces was found solely at higher stimulation frequencies (15 and 20 Hz). By contrast, lower frequency ssVEPs did not show this inversion effect. These findings suggest that stimulation frequency affects the sensitivity of ssVEPs to face inversion.